Stereoscopic Rendering via Goggles Elicits Higher Functional Connectivity During Virtual Reality Gaming - Forlim, Caroline Garcia; Bittner, Lukas; Mostajeran, Fariba; Steinicke, Frank; Gallinat, Jürgen; Kühn, Simone (Frontiers in Human Neuroscience, 2019)
Virtual reality (VR) simulates real world scenarios by creating a presence in its users. Such immersive scenarios lead to behavior that is more similar to that displayed in real world settings, which may facilitate the transfer of knowledge and skills acquired in VR to similar real world situations. VR has already been used in education, psychotherapy, rehabilitation and it comes as an appealing choice for training intervention purposes. The aim of the present study was to investigate to what extend VR technology can be used in a magnetic resonance imaging scanner (MRI), addressing the question of whether brain connectivity differs between VR stimulation and a presentation from a screen via mirror projection. Moreover, we wanted to investigate whether stereoscopic goggle stimulation, where both eyes receive different visual input, would elicit more brain connectivity than a stimulation in which both eyes receive the same visual input (monoscopic). To our knowledge, there is no previous research using functional MRI to address this question. Multiple analyses approaches were taken so that different aspects of brain connectivity could be covered: fractional low frequency fluctuation, independent component analysis, seed-based functional connectivity and graph analysis. In goggle presentation (mono and stereoscopic) as contrasted to screen, we found differences in brain connectivity in left cerebellum and postcentral gyrus as well as in the visual cortex and frontal inferior cortex (when focusing on the visual and default mode network). When considering connectivity in specific areas of interest, we found higher connectivity between bilateral superior frontal cortex and the temporal lobe, as well as bilateral inferior parietal cortex with right calcarine and right lingual cortex. Furthermore, we found superior frontal cortex and insula/putamen to be more strongly connected in goggle stereoscopic vs. goggle monoscopic, in line with our hypothesis. We assume that the condition that elicits most brain connectivity should be most suited for long-term brain training interventions given that, extended training under these conditions could permanently improve brain connectivity on a functional as well as on a structural level.